Radiating solitary waves in coupled Boussinesq equations. (25th May 2017) - Grimshaw, R. H. J.; Khusnutdinova, K. R.; Moore, K. R.
Abstract: In this article, we are concerned with the analytical description of radiating solitary wave solutions of coupled regularized Boussinesq equations. This type of solution consists of a leading solitary wave with a small-amplitude co-propagating oscillatory tail and emerges from a pure solitary wave solution of a symmetric reduction of the full system. We construct an asymptotic solution, where the leading order approximation in both components is obtained as a particular solution of the regularized Boussinesq equations in the symmetric case. At the next order, the system uncouples into two linear non-homogeneous ordinary differential equations with variable coefficients, one correcting the localized part of the solution, which we find analytically, and the other describing the co-propagating oscillatory tail. This latter equation is a fourth-order ordinary differential equation and is solved approximately by two different methods, each exploiting the assumption that the leading solitary wave has a small amplitude, and thus enabling an explicit estimate for the amplitude of the oscillating tail. These estimates are compared with corresponding numerical simulations.